The Statesman's Yearbook 2011
1608 p.
Keywords: Now in its 147th edition, The Statesman's Yearbook continues to be the reference work of choice for accurate and reliable information on every country in the world. Covering political, economic, social and cultural aspects, the Yearbook is an essential resource.